Gender Identity and Economic Decision Making - Anne Ardila Brenøe; Zeynep Eyibak; Lea Heursen; Eva Ranehill; Roberto A. Weber (Institute of Labor Economics (IZA), 2024)
Economic research on gender gaps has focused on variation based on the binary classification of "men" and "women". We explore whether a self-reported continuous measure of gender identity (CGI) explains variation in economic decisions and outcomes beyond the relationship with binary gender. We analyze data from four diverse populations (N=8,018), including measures of economic preferences and educational and labor market outcomes. We find that CGI is significantly associated with economic outcomes, with stronger relationships for men than women. Our results indicate that incorporating measures of self-reported gender identity could enhance our understanding of gender gaps in economic behavior and outcomes.
Keywords: C91; J16; J2; 330; gender identity; non-binary gender; economic preferences; economic outcomes